Development of Hybrid Energy Harvester for Self-Powered Environmental Sensor - Shaharizal, Syafiq (Universiti Teknologi PETRONAS, 2017)
The purpose of this research is to come out with a new type of energy harvester which is capable to produce higher output power as compared to the conventional energy harvester. This new model is known as hybrid energy harvester as it has both Piezoelectric and Magnetostrictive energy harvesters. The conventional energy harvester has some limitations i.e. it produces smaller output power and not quite sufficient to power up the low powered electronic devices, plus some of them only works in certain range of frequencies. With more than one energy harvesters are integrated, we can cover wider range of frequencies and able to increase the output power of this harvester. To construct the hybrid energy harvester, a mathematical model is first develop, then a simulation is carried out with MATLAB/Simulink. Circuit design and the prototype device are designed next. The mathematical model shows the basic concept of energy conversion from mechanical to electrical which is later simulated with MATLAB/Simulink.